Towards Discursive Justice: An Integrative Foucault-Islam Framework for Critical Media Discourse Analysis in Justice Issues - Qudratullah, Qudratullah; Nohong, Mursalim; Iqbal, Muhamad; Susanti, Ressi; Alkanan, Omer Mohamed Taha (IAIN Manado, 2025)
This research aims to analyze the construction of online media discourse in the